Avaliação do potencial antitumoral de dois novos complexos de rutênio (II) contendo alanina e triptofano em suas estruturas - Porto, Hellen Karine Paes (2012)
It is well known that metal complexes have been used as therapeutic agents since ancient times. However, with the success of cisplatin development as an antitumor agent in 1960inorganic drugs come to mainstream again. Despite the success of platinum compounds, serious problems are encountered when administering these drugs, such as nephrotoxicity, neurotoxicity and acquired resistance. In face of these problems other chemotherapeutic agents, less toxic to the organism and more efficient, become necessary. Several studies have been shown that ruthenium compounds present high selectivity for tumor cells and low systemic toxicity when compared to platinum (II) compounds. The present study evaluate antimor activity of two new ruthenium(II) compounds associated with amino acids, alanine and tryptophan. Ruthenium(II) compound were tested against B16-F10 and Ehrlich tumor cell lines and L-929 basal line using MTT assay, at different concentrations (0.2 - 200 mM) for 48 hours of treatment. Cell cycle analysis and apoptosis induction analyses by flow citometry and comet assay for DNA damage were also performed The IC50 values were estimated as 16.17 mM (RuAla) and 7.75 mM (RuTrp). The compound RuAla proved to be specific for the B16-F10 tumor cell line and showed a significant ability to change cell cycling profiles, arresting cells inG0/G1 phase, and also inducing cell death by apoptosis within 48 hours of treatment. The compound RuTrp showed high cytotoxic potential against Ehrlich tumor, interfering cell cycle kinetics,causing cell cycle arrest in G0/G1 phase and inducing cell death by apoptosis. Comet assay presented damage to genetic material only when cells were trated with high concentrations of RuTrp. , RuAla and RuTrp presented relevant cytotoxic activities towards tumor lineages tested in vitro. Thus, more specific tests are needed to elucidate the mechanism of action of these promising The ruthenium(II) compounds.